Weight management in the performance athlete - Manore, M. M. (Nutritional Coaching Strategy to Modulate Training Efficiency, 2013)
Management of weight is an ever-increasing challenge in societies where good tasting food is convenient, relatively inexpensive, and abundant. Developing a weight management plan is essential for everyone, including athletes that expend high amounts of energy in their sport. This brief review addresses the concept of dynamic energy balance and dietary approaches that can be successfully used with active individuals to facilitate weight loss, while retaining lean tissue and minimizing risks for disordered eating. Emphasis is placed on teaching athletes the benefits of consuming a low-energy-dense diet (e.g. high-fiber, high-water, low-fat foods), which allows for the consumption of a greater volume of food that is satiating but reduces energy intake. Other dietary behaviors important for weight loss or weight maintenance after weight loss are also emphasized, such as eating breakfast, spreading food and protein intake throughout the day, eating after exercise, elimination of sweetened beverages, and avoiding fad diets. As the general population becomes heavier, more young athletes will come to their sport needing to alter bodyweight or composition to perform at their peak. Health professionals need to be prepared with effective and evidence-based dietary approaches to help the athletes achieve their bodyweight goals.